2013
DOI: 10.1371/journal.pone.0078474
|View full text |Cite
|
Sign up to set email alerts
|

Activation of MSRV-Type Endogenous Retroviruses during Infectious Mononucleosis and Epstein-Barr Virus Latency: The Missing Link with Multiple Sclerosis?

Abstract: The etiology of multiple sclerosis (MS) is still unclear. The immuno-pathogenic phenomena leading to neurodegeneration are thought to be triggered by environmental (viral?) factors operating on predisposing genetic backgrounds. Among the proposed co-factors are the Epstein Barr virus (EBV), and the potentially neuropathogenic HERV-W/MSRV/Syncytin-1 endogenous retroviruses. The ascertained links between EBV and MS are history of late primary infection, possibly leading to infectious mononucleosis (IM), and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 58 publications
5
63
0
4
Order By: Relevance
“…2,3 In search of links between EBV and HERV-W/MSRV/ Syncytin-1, the expression of HERV-W/MSRV/ Syncytin-1 was studied in vitro, with/without exposure to EBVgp350 (the major protein of EBV envelope), on PBMC from healthy donors and MS patients, and on astrocytes, 5 and, in another study, in hospitalized young adults with infectious mononucleosis, and healthy controls, who were either EBV-negative or latently EBVinfected, with/without high titers of anti-EBNA-1 IgG. 16 The results showed that in vitro EBV activates the potentially immunopathogenic and neuropathogenic HERV-W/MSRV/Syncytin-1, in cells deriving from blood and brain. In vivo HERV-W/MSRV activation was higher in blood cells of patients with infectious mononucleosis, and in healthy controls with high anti-EBNA-1 IgG titers.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 In search of links between EBV and HERV-W/MSRV/ Syncytin-1, the expression of HERV-W/MSRV/ Syncytin-1 was studied in vitro, with/without exposure to EBVgp350 (the major protein of EBV envelope), on PBMC from healthy donors and MS patients, and on astrocytes, 5 and, in another study, in hospitalized young adults with infectious mononucleosis, and healthy controls, who were either EBV-negative or latently EBVinfected, with/without high titers of anti-EBNA-1 IgG. 16 The results showed that in vitro EBV activates the potentially immunopathogenic and neuropathogenic HERV-W/MSRV/Syncytin-1, in cells deriving from blood and brain. In vivo HERV-W/MSRV activation was higher in blood cells of patients with infectious mononucleosis, and in healthy controls with high anti-EBNA-1 IgG titers.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the data indicate that the two main links between EBV and MS (IM and high anti-EBNA-1-IgG titers) are paralleled by activation of the potentially neuropathogenic HERV-W/MSRV. Considering our data and those of the literature on MS pathogenesis, we postulate the possibility that EBV is an initial trigger of future MS, years later, and that MSRV has a direct role as effector of neuropathogenesis before and during MS [24,36].…”
Section: The Viral Trigger Of Ms Pathogenesis and The Dual Virus Hypomentioning
confidence: 52%
“…We verified whether HERV-W might be activated also in vivo, in hospitalized young adults with IM symptoms, and in healthy controls that were either EBV negative or latently EBV infected with or without high titers of anti-EBNA-1 IgG [24,36]. Briefly, the results showed that in vitro EBV activates the potentially immunopathogenic and neuropathogenic HERV-W/MSRV/syncytin-1 in cells deriving from the blood and brain.…”
Section: The Viral Trigger Of Ms Pathogenesis and The Dual Virus Hypomentioning
confidence: 73%
See 2 more Smart Citations